2016
DOI: 10.1242/dev.126516
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in developmental signalling

Abstract: In order to achieve coordinated growth and patterning during development, cells must communicate with one another, sending and receiving signals that regulate their activities. Such developmental signals can be soluble, bound to the extracellular matrix, or tethered to the surface of adjacent cells. Cells can also signal by releasing exosomes -extracellular vesicles containing bioactive molecules such as RNA, DNA and enzymes. Recent work has suggested that exosomes can also carry signalling proteins, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
145
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 151 publications
(196 reference statements)
0
145
0
2
Order By: Relevance
“…Exosomes have been implicated in the secretion, diffusion and signal transduction of the class of lipid-modified ligand, those of the Hedgehog family of secreted proteins [40]. Gradilla et al regarded a functional Hedgehog associated to heterogeneous exosomes, either originated from exosomes or/and directly shedding from the plasma membrane of cytonemes, and that are essential for Hedgehog gradient formation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes have been implicated in the secretion, diffusion and signal transduction of the class of lipid-modified ligand, those of the Hedgehog family of secreted proteins [40]. Gradilla et al regarded a functional Hedgehog associated to heterogeneous exosomes, either originated from exosomes or/and directly shedding from the plasma membrane of cytonemes, and that are essential for Hedgehog gradient formation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicle secretion involves 2 processes: the formation process, and the release process . Studies have shown that the RAB GTPase proteins are important regulators of intracellular vesicle transport, regulating vesicle trafficking at different stages, such as vesicle budding, vesicle and organelle flow, vesicle and accurate convergence, and fusion of cell membranes .…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicle secretion involves 2 processes: the formation process, and the release process. 26 Studies have shown that the RAB GTPase proteins are important regulators of intracellular vesicle transport, regulating vesicle trafficking at different stages, such as vesicle budding, vesicle and organelle flow, vesicle and accurate convergence, and fusion of cell membranes. 27,28 Sorting of cargo into EVs is a key step in the formation of EVs, which is regulated by a series of molecules, including endosomal sorting complex required for transport (ESCRT), 4 transmembrane protein CD63, and liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…Gradilla and co-workers showed that the transport of the morphogen hedgehog (Hh) is important for proper spatially restricted signalling during development [5]. The involvement of EVs in the developmental signalling was recently reviewed [6]. EVs secreted by cells present in a mature kidney were identified by studying urine samples.…”
Section: Introductionmentioning
confidence: 99%